2014
DOI: 10.4040/jkan.2014.44.1.86
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study using Mixed Methods on Foreign Residents' Satisfaction with Korean Health Care Services

Abstract: Purpose: This study was conducted to examine and compare satisfaction with Korean health care services for Americans, Chinese and Russians who resided in Korea. Methods: A questionnaire was distributed to 252 participants (81 Americans, 89 Chinese, 82 Russians). Three focus group interviews were subsequently conducted in order to obtain a greater understanding of participants' experience and perspectives. Results: The average satisfaction score was 3.09, with Americans and Russians showing significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…According to the measurement made using the same tool by the Korean Health Industry Development Institute [13], the overall satisfaction rate of foreign patients in Korea was 88.3, with 91.6 for Russia, 90.5 for the Middle East, 89.1 for the US, 88.2 for Southeast Asia, 88.0 for Mongolia, 85.3 for China and 80.4 for Japan. In the study by Kim and colleagues [21] which surveyed the satisfaction of American, Chinese and Russian patients living in Korea, Russia was 78.0, USA was 79.3 and China was 74.8. Compared to previous research results, the UAE government sponsored patients' satisfaction with Korean medical services was high, but in order to increase the attractiveness of Korean hospitals, continuous efforts are still needed to increase the satisfaction rate of medical services.…”
Section: Discussionmentioning
confidence: 99%
“…According to the measurement made using the same tool by the Korean Health Industry Development Institute [13], the overall satisfaction rate of foreign patients in Korea was 88.3, with 91.6 for Russia, 90.5 for the Middle East, 89.1 for the US, 88.2 for Southeast Asia, 88.0 for Mongolia, 85.3 for China and 80.4 for Japan. In the study by Kim and colleagues [21] which surveyed the satisfaction of American, Chinese and Russian patients living in Korea, Russia was 78.0, USA was 79.3 and China was 74.8. Compared to previous research results, the UAE government sponsored patients' satisfaction with Korean medical services was high, but in order to increase the attractiveness of Korean hospitals, continuous efforts are still needed to increase the satisfaction rate of medical services.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals are opening foreign patients' clinics within their institutions, developing dietary menus for inpatients, and employing medical tour coordinators and professional interpreters to accommodate the care of foreign patients [3]. Foreign patients reported satisfaction with the quality of care and nursing services provided in Korea; however, dissatisfaction with communication, patient education, culturally respectful services, and discriminatory attitude toward patients from Asian ethnic groups were also reported [4].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] The insufficient competency of health care providers in transcultural care is directly related to low patient satisfaction and negative health outcomes. [5] This may stem from miscommunication with patients or misunderstanding the common health problems of culturally diverse patients. Recent research has found that the quality of communication between physicians and patients can be hindered by miscommunication that arises from differences in perspectives, values, and beliefs about health and illness.…”
Section: Introductionmentioning
confidence: 99%